2004
DOI: 10.1111/j.1468-3083.2004.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising in long‐standing necrobiosis lipoidica

Abstract: Necrobiosis lipoidica (NL) is a disease of collagen. Squamous cell carcinomas developing in areas of chronic ulceration and scarring have been well documented in a variety of skin diseases but rarely in areas of necrobiosis lipoidica. The case history of a 76-year-old female is presented, whose squamous cell carcinoma appeared 30 years after the diagnosis of necrobiosis lipoidica. The clinical and histopathological picture is described, stressing the importance of the unusual association of the two pathologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 7 publications
0
18
0
3
Order By: Relevance
“…In this respect, most of our patients showed a lack of compliance or adherence, despite the psychological strain caused by the cosmetically disfiguring ulcerations and the pain. In addition, regular follow-up is necessary because it has been shown that long-standing chronic ulcerating lesions of necrobiosis lipoidica can lead to squamous cell carcinoma owing to malignant transformation as described in several case reports (28)(29)(30). In addition, an adequate pain therapy is necessary, because all patients in our group described their ulcerations as very painful.…”
Section: Treatmentmentioning
confidence: 88%
“…In this respect, most of our patients showed a lack of compliance or adherence, despite the psychological strain caused by the cosmetically disfiguring ulcerations and the pain. In addition, regular follow-up is necessary because it has been shown that long-standing chronic ulcerating lesions of necrobiosis lipoidica can lead to squamous cell carcinoma owing to malignant transformation as described in several case reports (28)(29)(30). In addition, an adequate pain therapy is necessary, because all patients in our group described their ulcerations as very painful.…”
Section: Treatmentmentioning
confidence: 88%
“…7.11). [463][464][465][466][467][468] The simultaneous occurrence of necrobiosis lipoidica with granuloma annulare 469,470 and with sarcoidosis has been reported. 424 However, granuloma annulare and sarcoidosis have been reported in the same patient.…”
Section: Histopathologymentioning
confidence: 99%
“…Further studies need to be carried out, with determination of skin thickness before and after treatment and comparisons with the changes seen after topical corticosteroid therapy of NL. Many skin diseases associated with chronic inflammation and scarring, including NL, may be associated with a long‐term risk of malignant transformation to squamous cell carcinoma 13 . Treatment of the lesion, even by a potentially carcinogenic therapy such as UVA1, may therefore reduce this risk, although further studies are required to investigate this.…”
Section: Reportmentioning
confidence: 99%